Wealth accumulation through home ownership: The painful myth of housing tenure, and what to do about it. Issue 1 (3rd March 2020) - Marcuse, Peter
Abstract : While homeownership is widely associated with a bundle of individual legal rights, it must be seen in relation to its social and political implications. This piece aims to differentiate the meaning and value of homeownership and make room for alternative tenures. Community Land Trusts are one promising alternative model. I argue that there is a great need to develop alternatives to homeownership and eventually to decommodify housing altogether.